(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: To determine of effectiveness of exclusive breastfeeding preparing program on knowledgeof primipara mothers in kirkuk city hospitalsMethodology: A quasi-experimental design of thirty Primipara women in three hospitals in kirkuk cityfor the period from March 1st to October 1st 2020.The data collected through stages which includepretest, posttest.Results: The finding indicate that among thirty study sample the MS and SD were higher in posttestin compare with pretest, and significant differences were found within study sample before and afterprogram at (P=0.05) which indicated that educational program positively effect on the study sampleregarding exclusive breastfeeding.Conclusions: The study concludes that after assessing the knowledge of the study sample, it found thattheir knowledge was poor and exclusive breastfeeding educational program was effectively improvedtheir knowledge.